Modeling the gameplay actions of elite volleyball players and teams based on statistical match reports - Sergii Iermakov; Tetiana Yermakova; Krzysztof Prusik (Pedagogy of Health)
Background and Study Aim. In modern sports analysis statistical modeling of gameplay actions based on match data is becoming a key tool for optimizing training processes and tactical preparation. The aim of the research is to create models of volleyball players' actions based on statistical reports of the 2022 World Championship matches.